Pronator quadratus repair after volar plating of distal radius fractures or not? Results of a prospective randomized trial. Issue 1 (December 2015) - Häberle, Sandra; Sandmann, Gunther; Deiler, Stephan; Kraus, Tobias; Fensky, Florian; Torsiglieri, Tobias; Rondak, Ina-Christine; Biberthaler, Peter; Stöckle, Ulrich; Siebenlist, Sebastian
Abstract Background The purpose of the present study was to investigate the influence of the pronator quadratus (PQ) muscle repair following volar plate fixation of distal radius fractures with special regards to the forearm pronation strength. During the early recovery period of 3 months, an improvement of pronation strength and functional scorings was hypothesized for the PQ repair when compared to no repair. Methods The inclusion criteria were (1) men or women between 18 and 80 years, (2) isolated, closed fractures of the distal radius, (3) A2 to B2 types of fracture according to the AO fracture classification system, (4) primary volar locking plate osteosynthesis. Patients were randomized to group A = PQ repair and group B = no repair. Follow-up examinations after 6 and 12 weeks included bilateral isometric pronation strength measurement, range of motion, theQuick DASH and the Mayo-Wrist-Score, and a visual analog scale (VAS). Results 60 patients (n  = 31 in group A andn  = 29 in group B) with an average age of 54 years (range 22–77 years) returned for both follow-up visits. The pronation strength measurements showed no significant differences between groups (PQ repair vs. no repair) neither at 6 weeks nor at 12 weeks. Additionally, no statistical significant differences were noted for ROM, Quick DASH-Score or Mayo-Wrist-Score. The VAS scoring revealed a significant decreased pain level after PQ repair at 6 weeks postoperatively (p  = 0.017). Conclusion An improved pronation strength after PQ repair in the early rehabilitation period could not be confirmed. However, the PQ repair might reduce pain in the early postoperative period. Trial registration number: NCT02595229 (ClinicalTrials.gov, registered 02 November 2015)